Analisis Daya Listrik Pada Jahe dalam Bentuk Bubur dan Larutan Ekstraksi - Fita Widiyatun; Sri Endang Wahyuni; Didik Nur Huda (STRING (Satuan Tulisan Riset dan Inovasi Teknologi), 2021)
Electrical energy is closely related to human life today. This is because many electronic goods can be used in the presence of electrical energy. The more population and needs for the electronic goods, more  greater the needs of electricity. Because this is very important, a study of electrical energy is needed. The purpose of this research is to calculate the electrical power stored in ginger, in the form of slurry and extraction solution. This research is an experimental research. The data taken is the amount of voltage and current with variations in the mass and type of ginger. The results obtained from this study are when the ginger is in the form of slurry, the largest electric power is in red ginger with a value of 180.3802 microWatt. Meanwhile, when it is in the form of extraction solution, the greatest value is found in emprit ginger with a power of 106, 3404 microWatt.